2019
DOI: 10.3390/ma12244196
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Surface Roughness after Lingual Bracket Debonding: An In Vitro Study

Abstract: The aim of the present study was to quantitatively assess changes in enamel roughness parameters before and after lingual bracket debonding. The lingual surface of 25 sound premolars extracted for orthodontic reasons was studied by 3D optical interferometric profilometry before and after debonding of lingual brackets following enamel finishing (with fine diamond) and polishing (with 12-and 20-fluted carbide burs). The roughness parameters tested were the amplitude parameters Sa and Sz, the hybrid parameter Sdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…The debonding procedure is simplified with the possibility to visualize composites remnants during their removal; the damage risks for lingual bracket debonding described in literature are minimized (Figure 6). 8 …”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The debonding procedure is simplified with the possibility to visualize composites remnants during their removal; the damage risks for lingual bracket debonding described in literature are minimized (Figure 6). 8 …”
Section: Case Reportmentioning
confidence: 99%
“…Although this technique is useful for composite and resin removal in visible areas such as the buccal surfaces, it becomes even more effective in the less accessible lingual areas. The lingual bracket debonding under natural or dental operating light can cause a significant increase of the enamel roughness 8 . The lingual surfaces have a greater interindividual morphological variability than the buccal surfaces; therefore, distinguishing enamel and resins of similar color is even more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the influence of polishing of cement remnants on the enamel surfaces has also been analyzed, and an increase of enamel roughness in both buccal [28] and lingual multibracket appliances was reported [9]; therefore, the polishing of cement remnants is still a challenge for clinicians [29]. Eichenberger et al reported 0.20 µm of enamel removed after cement polishing of the lingual multibracket appliance therapy [30], and Janiszewska-Olszowska et al reported 13.70 µm of enamel removed after cement polishing of the buccal multibracket appliance therapy with a tungsten carbide bur [8].…”
Section: Discussionmentioning
confidence: 99%
“…There is no gold standard on how to remove composite remnants after bracket debonding, but the tungsten carbide bur remains the most preferred tool [ 7 , 8 ]. The clean-up with the tungsten carbide bur is fast and effective, but results in an increased enamel roughness, which requires subsequent multistep polishing [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%